Perkembangan Sosial Anak dan Pengaruhnya Bagi Pendidikan : Ditinjau dari Kemampuan Emosional Anak - Hidayatul Hafiyah; Zainal Arifin (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2024)
The aim of this research is to explore theories of child sociological development, children's emotional abilities, factors that influence children's social-emotional development. This research is qualitative research with the type of library research. The findings from this research can be concluded: first, the characteristics of early childhood are as follows: (1) children have great curiosity, (2) children are unique, (3) children are rich in fantasy or imagination, (4) children have attitudes egocentric, (5) children have short concentration power. Second, there are four stages of children's social emotional development, namely: (1) development stage I from infancy to 2 years of age. The first stage is the baby's stage of learning about hope, (2) the second stage of development from 18 months to 4 years old. At this stage children will learn to face the conflict of independence vs shame, (3) stage III development from the age of 3 years to 6 years. In the third stage, children will learn to deal with emotions when the meaning is accepted or rejected, (4) stage IV development from the age of 5 and a half years to 12 years. This stage develops in school-age children. Here, children will learn how to compete in groups, developing 3 social skills. Third, social development factors can be influenced by: (1) family, (2) maturity, (3) socio-economic status, (4) education, (5) mental capacity: emotions and intelligence.